2020
DOI: 10.7554/elife.58243
|View full text |Cite
|
Sign up to set email alerts
|

Distinct interactions of eIF4A and eIF4E with RNA helicase Ded1 stimulate translation in vivo

Abstract: Yeast DEAD-box helicase Ded1 stimulates translation initiation, particularly of mRNAs with structured 5'UTRs. Interactions of the Ded1 N-terminal domain (NTD) with eIF4A, and Ded1-CTD with eIF4G, subunits of eIF4F, enhance Ded1 unwinding activity and stimulation of preinitiation complex (PIC) assembly in vitro. However, the importance of these interactions, and of Ded1-eIF4E association, in vivo were poorly understood. We identified separate amino acid clusters in the Ded1-NTD required for binding to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
55
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(58 citation statements)
references
References 37 publications
3
55
0
Order By: Relevance
“…Shorter, unstructured 5'UTRs enable more efficient translation, and secondary structures like Gquadruplexes and stable hairpins have been shown to robustly repress translation by inhibiting preinitiation complex scanning (Arora et al, 2008;Beaudoin and Perreault, 2010;Davuluri et al, 2000;Endoh and Sugimoto, 2016;Halder et al, 2009;Kozak, 1991;Sample et al, 2019). Further, multiple RNA helicases operate during translation initiation to assist in scanning through long and structured 5'UTRs (Gulay et al, 2020;Parsyan et al, 2011;Popa et al, 2016;Rubio et al, 2014;Sen et al, 2019;Sen et al, 2015;Soto-Rifo et al, 2012;Svitkin et al, 2001;Waldron et al, 2019;Wolfe et al, 2014). Despite the well-characterized repression of protein biogenesis associated with impeding progression of scanning ribosomes, the molecular rationale for this repression remained uncharacterized.…”
Section: Discussionmentioning
confidence: 99%
“…Shorter, unstructured 5'UTRs enable more efficient translation, and secondary structures like Gquadruplexes and stable hairpins have been shown to robustly repress translation by inhibiting preinitiation complex scanning (Arora et al, 2008;Beaudoin and Perreault, 2010;Davuluri et al, 2000;Endoh and Sugimoto, 2016;Halder et al, 2009;Kozak, 1991;Sample et al, 2019). Further, multiple RNA helicases operate during translation initiation to assist in scanning through long and structured 5'UTRs (Gulay et al, 2020;Parsyan et al, 2011;Popa et al, 2016;Rubio et al, 2014;Sen et al, 2019;Sen et al, 2015;Soto-Rifo et al, 2012;Svitkin et al, 2001;Waldron et al, 2019;Wolfe et al, 2014). Despite the well-characterized repression of protein biogenesis associated with impeding progression of scanning ribosomes, the molecular rationale for this repression remained uncharacterized.…”
Section: Discussionmentioning
confidence: 99%
“…The 3’ UTR is considered important for SRP-dependent targeting of mRNAs [reviewed by (76)]; but the SRP is not known to directly interact with the mRNA, and it may interact through another RNA binding protein (77). Ded1 (and DDX3) could serve this role as it interacts with both 5’ and 3’ components of the mRNA [(13,16) and references therein]. Ded1 remains attached to the mRNA during scanning by the 43S ribosomes, assembly of the 48S ribosomes and eventual formation of the 80S ribosomes at the AUG start codon (Figure 15A).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the functional activity of Ded1 is conserved throughout eukaryotes. Ded1 is considered a general translation-initiation factor that is important for 43S ribosome scanning to the initiation codon and formation of the 48S complex at the AUG codon [ (14)(15)(16) and references therein]. We have shown that Ded1 is a cap-associated factor that actively shuttles between the nucleus and cytoplasm using both the XpoI/Crm1 and Mex67/TAP nuclear pore complexes (13).…”
mentioning
confidence: 99%
“…Results from both reporter assays and ribosome profiling (Ribo-seq) studies are consistent with this proposal, showing that transcripts vary in their sensitivity to DDX3X/Ded1 depending on the extent of predicted structure in their 5’ UTRs ( 18 , 20 , 21 , 22 ). DDX3X/Ded1 also associates with the eIF4F translation complex, which binds to the mRNA early in PIC assembly, and it appears to have a role in this process, again in an mRNA-specific fashion ( 19 , 23 , 24 , 25 , 26 ).…”
mentioning
confidence: 99%